Influence of Training and Honorarium on the Work Effectiveness of Employees at the Regional Secretariat Procurement of Goods and Services Division, North Konawe Regency Government - Hasid, Alkadri; Muthalib, Abd Azis; Lisapaly, David C.E. (PT. Riset Press International, 2024)
This study aims to analyze the influence of training and honorarium on the work effectiveness of employees at the Regional Secretariat Procurement of Goods and Services Division, North Konawe Regency Government. There are still deficiencies in the external equity of honorarium, creating uncertainty and disappointment among employees. This study seeks to answer whether training and honorarium affect employee work effectiveness. The research methodology used is descriptive methods and multiple linear regression analysis with a sample size of 31 employees. The main results of the study indicate that training and honorarium have a positive and significant effect on employee work effectiveness. Employees perceive the provided training and honorarium as highly satisfactory, which implicates an improvement in work effectiveness. Good training enhances employees' knowledge and skills, while fair honorarium motivates employees to work more effectively. The implications of this study suggest that improvements in the training and honorarium system can enhance employee work effectiveness in the institution.